Perbedaan Kualitas Kimiawi Kefir Susu Sapi, Susu Kedelai, Dan Susu Kacang Merah - Thauhidayatul Hidayah (SainsTech Innovation Journal, 2019)
Kefir is obtained through the fermentation process of milk using a starter in the form of kefir grains containing Streptococcus sp., Lactobacilli and several types of nonpatogenous yeast. Generally the ingredients for making kefir come from animal milk. However, most people are very allergic to animal milk. For this reason, this research tries to make fermented milk derived from vegetable milk, which is derived from soy milk and red bean milk. The purpose of this study was to determine the pH, lactic acid concentration, alcohol content, and organoleptic test results in kefir derived from cow's milk, soy milk, and red bean milk. The study was conducted with a three-repetition treatment design. The parameters in this study include pH, alcohol content, lactic acid levels, and organoleptic. Data obtained from each kefir were compared with SNI standards on processed milk products (fermentation). Alcohol test results obtained from kefir from cow's milk, soy milk, and red bean milk were 4.95%, 5.54%, and 3.52%, respectively. Lactic acid levels of cow's milk, soy milk, and red bean milk were 0.12375%, 0.04878%, and 0.07128%, respectively. The pH of the three kefir is 3. Based on these results it can be concluded that the highest alcohol is found in kefir from soy milk, which is 5.54%; The highest levels of lactic acid are found in kefir from cow's milk, which is 0.12375%; c) pH tends to be the same for 3. Based on comparative analysis with SNI, that the three kefir do not meet SNI so that it is not yet feasible to be traded and to be produced on a large scale.